The influence of interactive digital learning media on improving history learning comprehension in grade IV students. - Asbah, Jamilahtul; Firdaus, Fery Muhamad; Fathurrohman, Fathurrohman (Jurnal Prima Edukasia, 2025)
The application of Digital Interactive Learning Media in the fourth grade of SDN 001 Tarempa aims to enhance students' understanding of historical material, which is crucial for building awareness of national identity and culture. However, students often face challenges in conventional history learning, such as a lack of interest and engagement, leading to low comprehension. This study employs a quantitative approach with an experimental design, where data is collected through tests to measure understanding, questionnaires to observe student responses, and observations of the learning process. It is hoped that the results of this research will demonstrate the effectiveness of interactive learning media in improving students' historical comprehension and contribute significantly to the development of more engaging and effective teaching methods at the elementary education level.